The Reaction of Thiol Compounds with the Vitamin-K Dependent Clotting Factors - Fantl, P (Thrombosis and Haemostasis, 1969)
Treatment of human and dog oxalated plasma with 0.2 to 1.0 × 10−1 M 2.3-dithiopropanol (BAL) or dithiothreitol (DTT) at 2–4° C for 30 min results in the reduction of the vitamin-K dependent clotting factors II, VII, IX and X to the respective-SH derivatives. The reaction is pH dependent. Under aerobic conditions the delayed one stage prothrombin time can be partly reversed. Under anaerobic conditions a gradual prolongation of the one stage prothrombin time occurs without reversal.In very diluted plasma treated with the dithiols, prothrombin can be converted into thrombin if serum as source of active factors VII and X is added. In contrast SH factors VII, IX and X are inactive in the specific tests. Reoxidation to active factors II, VII, IX and X takes place during adsorption and elution of the SH derivatives. The experiments have indicated that not only factor II but also factors VII, IX and X have active-S-S-centres.